Зернофуражные культуры - Ахметшин Ханиф Салихович (Башкирское книжное издательство, 1980)
Экземпляры: КХ (20120709) / Инвентарный номер: 0250190 / Цена: 0.10 / Сис.шифр: 633.1 / Авт.знак: А 95 / ГРНТИ: 68 / ББК: 4